Analisis Hasil Belajar: Dampak Pembelajaran Berbantuan Software pada Pembelajaran Statistika - Novalia, Novalia (Desimal: Jurnal Matematika, 2019)
This study aims to determine the effect of using Excel and SPSS on student learning outcomes in advanced statistics courses. This type of research is quantitative research with experimental research designs. The action taken is an effort to develop learning technology, namely the constructivism learning approach that is packaged in statistical learning through the use of Excel and SPSS. Based on the analysis of learning outcomes data from statistical learning without the help of programs, with the help of Excel and SPSS programs, there is no significant effect of using Excel and SPSS programs on student learning outcomes. There are several things that cause the use of Excel and SPSS programs do not affect student learning outcomes, namely (1) Inadequate infrastructure, (2) students 'basic statistical skills are still low and (3) students' interest in learning statistics is still low.